Retinal Histopathology in Eyes from a Patient with Stargardt disease caused by Compound Heterozygous ABCA4 Mutations. (2nd April 2016) - Bonilha, Vera L.; Rayborn, Mary E.; Bell, Brent A.; Marino, Meghan J.; Fishman, Gerald A.; Hollyfield, Joe G.
Abstract: Background : The goal of this study was to define the histopathology of the retina in donor eyes from a patient with Stargardt disease (STGD1) due to compound mutations in the ABCA4 gene. Materials and Methods : Eyes were obtained from a 66-year-old female and fixed within 18 hours postmortem. The fundi of the posterior globes were evaluated with macroscopic, SLO and OCT imaging. The perifoveal and peripheral regions were processed for electron microscopy and immunocytochemistry using cell specific antibodies. Two age-similar normal eyes were used as controls. Prior ophthalmic examinations and genetic test results were also reviewed. Results : All imaging modalities showed scattered bone spicules in the peripheral retina. Atrophy of the RPE was present around the optic nerve as evidenced by the absence of SLO autofluorescence. Histology analysis showed a severely degenerated fovea with little evidence of any retinal layering or remaining RPE. The fovea was severely degenerated, with little evidence of any retinal cell layer, including the RPE. In contrast, retinal nuclear layers were present in the periphery. The perifoveal region contained few cones labeled with cone-specific antibodies; some rhodopsin-labeled cells, reactive glia labeled with GFAP; and decreased autofluorescence of the RPE. The fovea was free of cone-specific labeling, contained a few disorganized rhodopsin-labeled cells and showed substantial GFAP labeling and no autofluorescent material in the retina. The periphery displayed stubby cells labeled with cone-specific antibodies, decreased rhodopsin-labeled cells, increased GFAP staining, and autofluorescent granules in the RPE. Conclusions : The histopathology of the retina in this patient with Stargardt disease displayed a highly degenerated fovea. In all retinal locations studied, cones were more severely affected than rods.